Assessing the physical performance of underwater rugby world champions: A comparative analysis between expert and novice players (2023)
ABSTRACT: Introduction: While previous studies have primarily focused on the perceptual and cognitive abilities of expert and novice players, the literature on underwater rugby (UWR) lacks studies on the physical elements influencing performance. This gap in knowledge necessitates a physical perspective to establish benchmarks set by experts, serving as crucial references for scientists as well as players aspiring to achieve peak levels in this sport. Objectives: The primary goal of this study was to conduct a comprehensive comparison between UWR experts and novices, specifically examining their performance in aerobic and anaerobic power, fatigue index, maximum strength, nonlinear underwater displacement, flexibility, and body composition. Methods: A total of 24 male players, consisting of 11 experts (World Champions, Austria 2019, Tier 5) and 13 novices (Tier 2), participated in this descriptive, quantitative, and nonexperimental study. The evaluation encompassed a diverse set of assessments, including Course Navette tests, sprint-based running, static maximal strength, flat bench press maximal strength, underwater direction change, shoulder flexibility, and bioimpedance. The tests were conducted over a 14-day period, ensuring optimal recovery between each assessment. Results: Anthropometric variables did not exhibit statistically significant differences between the expert and novice groups. However, significant variations were observed in various physical variables such as maximum force in the flat bench press, maximum power, minimum power, average power, fatigue index, and nonlinear displacement. Particularly significant were the large effect sizes observed in nonlinear underwater displacement, mean power, and maximum force in the flat bench press. Conclusions: The identified variables emerged as pivotal determinants of high performance in UWR. This comparative analysis between expert and novice players provides valuable insights for practitioners and sport scientists. It offers a foundation for the development of more effective research projects and targeted training programs, specifically designed to enhance performance in UWR.